Pengaruh Penambahan Dedak Padi dan Lactobacillus plantarum 1BL-2 dalam Pembuatan Silase Rumput Gajah (Pennisetum purpureum) - R Ridwan; S Ratnakomala; G Kartina; Y Widyastuti (Media Peternakan, 2005)
Silages making is a solution to overcome the shortage or excessive of forages in Indonesia. The objective of this study was to evaluate the effect of rice bran as carbohydrate source and Lactobacillus plantarum 1BL-2 addition on the quality of napier grass (Pennisetum purpureum) silages. The concentrations of rice bran and Lactobacillus plantarum 1BL-2 added were 0%,1%, 3% and 5 % (w/w) and incubated for 30 days. The results showed that the addition of 1%-5% rice bran significantly affected (P